Analyzing multigroup data with structural equation models - Nicole Görz; Lutz Hildebrandt; Dirk Annacker (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2000)
In empirical applications of structural equation modeling researchers often assume that the sample under investigation is homogenous unless observed characteristics allow for a division of the sample into mutual exclusive homogenous subgroups. If such information is not available, unobserved heterogeneity can be taken into account by a finite mixture approach (Arminger et al. (1998); Jedidi et al. (1997)). The simulation study presented in this paper reveals that this approach clearly out performs a sequential procedure combining cluster and multigroup analysis.
urn:nbn:de:kobv:11-10047154
Keywords: 330